Magnetic resonance imaging modalities aid in the differential diagnosis of atypical parkinsonian syndromes - Tinaz, Sule (Frontiers in Neurology, 2023)
Accurate and timely diagnosis of atypical parkinsonian syndromes (APS) remains to be a challenge. Especially early in the disease course, the clinical manifestations of the APS overlap with each other and with those of idiopathic Parkinson’s disease (PD). Recent advances in magnetic resonance imaging (MRI) technology have introduced promising imaging modalities to the clinical and research fields that aid in the diagnosis of APS. Some of these MRI modalities are also included in the updated diagnostic criteria of APS. Importantly, MRI is safe for repeated use and more affordable and accessible compared to nuclear imaging. These advantages make MRI tools more appealing for diagnostic purposes. As the MRI field continues to advance, the diagnostic use of these techniques in APS, alone or in combination, would be expected to become commonplace in clinical practice.